Composite of the recycled polypropylene reinforced with oil palm empty fruit bunch - Thaomadaran, Ghunavathy (2011)
This study is about the composite of recycled polypropylene reinforced with empty fruit bunch (EFB) fiber chopped into different length. The optimum weight percentage of EFB that gives higher strength and the effect of coupling agent on the composite are determined. The composite is prepared using EFB fiber with recycled polypropylene with weight percentage from ! wt to wt . Samples are prepared using extruder at ! C temperature with screw speed 70 rpm. The melt flow indexes (MFI) of the extruded samples are determined. Samples then injection moulded into dumb-bell specimen for testing and analysis. From the tensile testing, composite which has 30 wt% and 40 wt% of EFB shows optimum elongation modulus. The recycled polypropylene/ fiber composite with 30 wt% and 40 wt% EFB are prepared by adding coupling agent (MAPP) with fiber and MAPP ratio (10:1). Stress-strain properties of the composite are analyzed. The reinforcing property of the recycled polypropylene/ EFB fiber composite with and without coupling agent is compared.